Delivering Social Protection in the Midst of Conflict and Crisis : The Case of Yemen - Al-Ahmadi, Afrah Alawi; de Silva, Samantha (World Bank, Washington, DC, 2018)
Despite a situation of an active violent conflict, the Yemen Emergency CrisisResponse Project continues to deliver services and cash to the poor and vulnerablenationwide. This paper captures lessons learned from this innovative and pioneering project,which will be particularly relevant for shaping the World Bank's crisis response under IDA 18.